Research and application of broadband speed-up technology based on IPTV - Honggang ZHAO; Chunhui SONG; Dongsheng LIAN (Dianxin kexue)
With the increasing competition of broadband business homogenization and the explosive growth of IPTV users,differentiated products and service promotion are particularly important in the market competition.The development of IPTV industry and the technology of broadband speed-up technology was introduced,the core business process of broadband speed technology based on IPTV was expounded.Research results show that IPTV-based broadband speed-up technology can provide users with convenient and dynamic bandwidth adjustment services to meet the requirements of broadband bandwidth and IPTV users’ personalized bandwidth,the differentiation service advantage can be established,the risk of losing customers was reduced,the value of broadband and IPTV users is promoted.